Platinum Metal Complexes of Carbaboranylphophines: Potential Anti Cancer Agents - Ilham Maulana Ilham Maulana; Peter Loennecke Peter Loennecke; Evamarie Hey-Hawkins Evamarie Hawkins (ISCC (Indonesian Journal of Cancer Chemoprevention))
Polyhedral heteroboranes in particular dicarba-closo-dodecaboranes(12) and their organic derivatives have been the subject of intense research for over 40 years due to their unique chemical and physical properties. The initial attraction to dicarba-closo-dodecaboranes(12) In the medicinal chemistry research, was a result of their high boron content and stability to catabolism, which are important criteria for cancer therapy, such as BNCT (boron neutron capture therapy) agents. The coordination compounds of the platinum group metals have also received large interest for their potential application as chemotherapeutic agents, since cis-diamminedichloroplatinum(II), cisplatin, has been reported to have  capability as tumor inhibitor. Hence, applications can be envisioned for related cis platinum complexes. Complex of cis-rac-[PtCl2{1,2-(PRCl)2C2B10H10}] (R=Ph, tBu, NEt2, NPh2) have been synthesized by employing known carbaborane based phosphine ligands of clorophoshino-closo-dodecaborane , with complex of cis-[PtCl2(COD)] (COD = 1,5-cyclooctadiene) in an N2-atmosphere. The obtained complexes possess expected structure configuration, namely cis-rac. The characterization of the complex has been carried out using 1H, 31P, 13C and 11B-NMR (Nuclear Magnetic Resonance), X-ray of single crystals, elemental analysis, IR (infra red) and mass spectroscopy (MS). The 31P{1H} NMR spectra of all the platinum complexes distinctly show the typical platinum satellites which are attributed to 31P-195Pt-coupling, in which the 31P{1H} NMR spectrum exhibits three lines with an intensity ratio of ca.1:4:1. The structure of the platinum complexes consists of a slightly distorted square-planar coordination sphere, in which the platinum atom is bonded to two chlorides and two phosphorus atoms of the chelating carbaboranylphosphine. Thus the platinum atoms exhibit the coordination number four, which is preferred in platinum(II) complexes. Keywords: Platinum complexes, phosphine ligand, carbaborane